PENGARUH CITRA RUMAH SAKIT DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PASIEN DI RUMAH SAKIT IBU DAN ANAK SITTI KHADIJAH GORONTALO - NURYANTI ANTUKAY; Yolanda Ngabito; Imelda Mohammad (Journal of Health, Technology and Science (JHTS), 2022)
This study aims to determine the effect of hospital image and service quality on patient loyalty at the Sitti Khadijah Mother and Child Hospital, Gorontalo City . This study aims to determine whether there is an effect of hospital image and quality of service on patient loyalty in inpatient pediatric, internal and postpartum rooms, as seen from human resources, health services and also the facilities in RSIA. This type of research uses a quantitative approach. The type of data used Cross- sectional which aims to analyze the influence between the independent variables consisting of (hospital image and quality of service) and the dependent variable (patient loyalty) at RSIA Sitti Khadijah, Gorontalo City. The sample of this study was 40 people consisting of patients and their families. Data collection used a questionnaire which was then analyzed using the chi-square test The results showed that the influence of hospital image and service quality on patient loyalty obtained a pvalue of 0.04 because it was significantly less than 0.05 (0.04 ˂ 0.05). So it can be concluded that H1 is accepted and H0 is rejected because the significant value obtained is less than ˂ 0.04 from the results above that hospital image and service quality affect patient loyalty in the inpatient ward of Sitti Khadijah Mother and Child Hospital, Gorontalo City